Myelitis or transverse myelopathy. A case presentation. - Rubén Bembibre Taboada; Dianarelys Villafuerte Delgado; Annia Alvarado Borges; Niurka Galende Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Here is presented a brief information about the most relevant aspects of myelitis or transverse myelopathy, a syndrome of low frequency rates in our medical experience with intensive care, along with an assisted case in our clinic intensive therapy service. The patient was subjected to the diverse complementary tests, necessary for the diagnosis, and she received established treatment for this process, and so for the complications presented. It was proved a fulminant ascendant myelitis with unfavourable fast evolution.